Dinamika skupinskega odločanja in finančna kriza - Jezernik, Živa (Naše gospodarstvo, 2014)
Standard models of economic theory are largely focused on individual decision-making processes. Only in recent years have the awareness that many economic decisions are made by groups such as boards, committees, or families been strengthened. Thus, group decision-making is becoming an increasingly important topic of economic research. The disadvantages of group decision making are most visible in periods of exceptional circumstances, such as during the financial crisis that started in 2008. Given that the corporate governance of financial institutions is often identified as one of the main reasons for the current financial crisis and that the governance of banks and other financial institutions is based on group decision-making processes, we focus on the dynamics of group decision making and its impact on the formation and development of the financial crisis. In this paper, we present the findings of the prevailing theories from the field of social, cognitive, and experimental psychology and explain the differences between individual and group decision making, emphasizing the theories of risky shift and groupthink. This is followed by a review of economic studies of group and individual decision making as well as am analysis of the impact of collective decision making on the formation and development of the financial crisis.
Keywords: krize; ekonomska kriza; upravljanje; management; odločanje; skupine; teorija odločitev